Assessing the effect of surface states of mesoporous NiO films on charge transport and unveiling an unexpected light response phenomenon in tandem dye-sensitized solar cells. (19th April 2022) - Cheng, Haoliang; Ayaz, Muhammad; Wrede, Sina; Boschloo, Gerrit; Hammarström, Leif; Tian, Haining
Abstract : The effect of surface states of mesoporous NiO films on charge transport and an unexpected light response phenomenon in tandem dye-sensitized solar cells has been investigated. Abstract : In this paper, the role of NiO surface states is assessed in a tandem dye-sensitized solar cell (t-DSSC) consisting of a 4-(Bis-4-[5-(2, 2-dicyano-vinyl)-thiophene-2-yl]-phenyl-amino)-benzoic acid (P1) dye-sensitized NiO photocathode, a VG1-C8 dye-sensitized TiO2 photoanode and the I − /I3 − redox couple. The NiO surface states are proved to participate in the reduction of the I − /I3 − electrolyte in the t-DSSCs. By adjusting the thickness of the TiO2 film, the charge transport processes of the t-DSSCs are significantly affected by the photocurrent and the NiO surface states, resulting in various photovoltaic properties. This work also proves that the NiO surface states together with energy transfer between the desorbed P1 dye from the NiO photocathode and the VG1-C8 dye from the TiO2 photoanode are responsible for the light response from both dyes observed in the IPCE spectra of the t-DSSCs.